Associação de técnicas conservadoras na recuperação do sorriso - Franco, Laura Molinar [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
A patient presented with a chief complaint of spaces between the maxillary front teeth after completion of orthodontic treatment. A complete analysis of the patient's oral condition resulted in a treatment plan consisting of removal of orthodontic brackets, bleaching of the teeth of the maxillary and mandibular arch with Opalescense 10% (Ultradent Products, Inc., South Jordan, USA ), followed by closing of the diastemas with resin composite, Amelogen Plus (Ultradent Products Inc). This case demonstrates that a triage of orthodontic treatment, tooth whitening and conservative non-invasive restorative adhesive dentistry can restore shape, function and esthetics, resulting in a pleasing smile and improved self-confidence on the part of the patient

Relato de caso clínico de um paciente do sexo masculino, adolescente, que apresentava como queixa principal espaços interdentais generalizados no segmento anterior superior, após o término de tratamento ortodôntico. Após análise e discussão das condutas clínicas a serem adotadas foi proposto a realização do clareamento dental com peróxido de carbamida 10% (Opalesence - Ultradent Products, Inc., South Jordan, USA)e o fechamento dos diastemas anteriores com resina composta microparticulada Amelogen (Ultradent Products, Inc., South Jordan, USA). Observamos que a associação de tratamentos ortodônticos, clareadores e restauradores foram capazes de devolver a forma, função e estética dental, de nosso aciente adolescente
Keywords: Ortodontia; Diastema; Clareamento dental; Resinas compostas; Orthodontics